(untitled) (Journal of Rangpur Medical College, 2025)
Background: Human chorionic gonadotropin (HCG) has an important role in maintaining early pregnancy and has been studied to improve pregnancy outcomes. Objective: This study aimed to assess the effectiveness of a single 5,000 IU dose of HCG in improving early pregnancy outcomes for women at risk of complications. Methods: This prospective study was conducted at the Salauddin Specialized Hospital, Dhaka, Bangladesh, from January 2023 to January 2024 on 120 pregnant women in the early stages of pregnancy at 6 weeks without cardiac pulsation and positive β-hCG levels. They were randomly divided into two groups: the HCG group (n=60), which received 5,000 IU of intramuscular HCG, and the control group (n=60), who received standard care. The main outcomes included ongoing pregnancy rates, miscarriage rates, positive HCG levels, fetal heartbeat detection at 8 weeks, and hormone levels measured on day 5 after the injection. Results: The ongoing pregnancy rates were higher in the HCG group compared to the control group (86.7% vs. 70.0%, p=0.03). The miscarriage rate was lower in the HCG group (13.3% vs. 30.0%, p=0.03). Those who received HCG also had a higher chance of fetal cardiac pulsation positivity (83.3% vs. 66.7%, p=0.04) and a lower incidence of threatened abortion (10.0% vs. 23.3%, p=0.05). Biochemical analysis revealed higher levels of β-hCG (>1,500 IU/L; 91.7% vs. 71.7%, p=0.01) and progesterone (>10 ng/mL; 83.3% vs. 65.0%, p=0.02). We found weak-to-moderate correlations (r=0.25–0.34, p<0.05) linking HCG to positive outcomes, indicating its role in maintaining pregnancy. Conclusion: Administering a single dose of HCG significantly improved early pregnancy (at 6 weeks without cardiac pulsation and positive β-hCG levels) outcomes by providing better hormonal support and reducing complications. These results suggest that HCG supplementation may be helpful for women at risk of early pregnancy loss, though further large-scale studies are necessary. J Rang Med Col. 2025 Sep;10(2): 115-120